TRADISI OMED-OMEDAN SEBAGAI PENDIDIKAN KARAKTER BAGI TERUNA-TERUNI BANJAR KAJA DALAM RANGKAIAN HARI RAYA NYEPI DI KELURAHAN SESETAN DENPASAR SELATAN - Ni Made Yuni Artini; Ida Bagus Nyoman Wartha (Jurnal Santiaji Pendidikan (JSP), 2015)
Balinese always preserve cultural traditions as the inheritance of their ancestors. Omed-omedan tradition is a unique and rare tradition since such tradition cannot be encountered in other areas. Therefore, it is interesting to be discussed in a paper. This reseacrh was aimed at finding out: How is the process of implementation of Omed-omedan tradition at Banjar Kaja Kelurahan Sesetan, South Denpasar Sub-District, Denpasar City?, What is the relationship between Omed-omedan tradition and the series of Nyepi Holiday at Banjar Kaja Kelurahan Sesetan, South Denpasar Sub-District Denpasar City? What is the meaning of Omed-omedan tradition for the people at Banjar Kaja Kelurahan Sesetan, South Denpasar Sub-District, Denpasar City? The theoretical bases applied in this research are 1). Culture, 2). Religious systems, 3). Society. The results of the research show that the implementation of Omed-omedan Tradition must be conducted as it relates to Ida Bhatara Sesuhunan at in Banjar Kaja Sesetan temple, which is believed to be able to provide safety for His people, in addition, Omedomedan tradition is also an event of Masima Krama (visit and forgive each other) to welcome Caka New Year (Nyepi Holiday). The conclusions of this research are 1). Omed-omedan tradition is Purwa Dresta, namely a religious custom and it is not allowed if it is not conducted because if it is not conducted, it is believed it would lead to the undesirable things, 2). In its performance, Omed-omedan tradition is an event of Masima Krama in order to welcome Caka New Year, 3). The meaning of this Omed-omedan tradition is as a devotion to Ida Bhatara Sesuhunan, as by always conducting this tradition, the members of Banjar Kaja Sesetan are believed to always have His protection.